2021
DOI: 10.1007/s12639-021-01446-2
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Schistosoma haematobium infection by microscopy and polymerase chain reaction (PCR) in school children in three senatorial districts of Cross River State, Nigeria

Abstract: As a result of the poor sensitivity and speci city of the standard parasitological diagnostic methods currently being used, this study was conducted to compare the standard parasitological diagnostic methods and Polymerase Chain Reaction (PCR) in determining the prevalence of urinary schistosomiasis in Cross River State (CRS). The study was conducted between April 2015 and March 2016. Seven hundred and seventy seven (777) urine samples were randomly collected from selected school-age children. The urine sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Every year, hundreds of articles are published on schistosomiasis. Table 2 summarizes the recently reported prevalence of UGS in SSA that was indexed in PubMed [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Recent Status Of Ugs In Sub-saharan Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Every year, hundreds of articles are published on schistosomiasis. Table 2 summarizes the recently reported prevalence of UGS in SSA that was indexed in PubMed [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Recent Status Of Ugs In Sub-saharan Africamentioning
confidence: 99%
“…As shown in Table 2 , most surveys screened SAC following WHO recommendations, which is a cost-effective approach and well reflects endemicity in the surveyed locality [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Recent Status Of Ugs In Sub-saharan Africamentioning
confidence: 99%
See 1 more Smart Citation
“…В исследовании при сравнении со стандартными методами паразитологической диагностики ПЦР показывает значительное увеличение распространенности заболевания [67]. Так, в исследовании ПЦР позволила выявить на 13-15% больше случаев инвазии по сравнению с микроскопией [68]. C помощью усовершенствования методов экстракции ДНК из образцов чувствительность метода может достигать 100%.…”
Section: молекулярно-генетические методыunclassified
“…However, this approach may lead to the potential underdiagnosis of the disease because eggs can be excreted intermittently-leading to false negative results-and because patients with low-intensity infections may not have enough eggs excreted in their urine to be detectable under the microscope after conventional processing methods [9]. Indeed, studies have confirmed that standard urine filtration microscopy (UFM) detects far fewer cases of S. haematobium infection compared to molecular methods [10,11].…”
Section: Introductionmentioning
confidence: 99%